Analisis Kuat Tekan Dan Penyerapan Air Menggunakan Pasir Tailing Timah Dan Kaolin: Analysis of Compressive Strength and Water Absorption Using Tin Tailings Sand and Kaolin - Zikri, Ummi Athiyyah; Hisyam, Endang Setyawati (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2023)
The environmental damage resulting from mining not only eliminates soil fertility but changes the landscape of the existing ecosystem and produces waste such as tailings and kaolin and understory. The results of tin and kaolin tailings mining have not been utilized optimally. This research aims to analyze the effect of using tin tailings sand and kaolin on bricks which produces compressive strength and water absorption in accordance with standards. The method used is to take tin and kaolin tailings mixed with clay with a predetermined composition and tested in the laboratory. Based on the test results, the compressive strength value obtained meets the standards, namely the percentage of 15% tin tailings sand and 10% kaolin, the compressive strength value is 5,150 Mpa. The water absorption value using percentages of 5%, 10% and 15% tin tailings sand and 10% kaolin has met the specified standards.